Balloon sandwich technique for retrieval of fractured delivery wire of pipeline stent. Issue 1 (February 2018) - Cerejo, Russell; Bain, Mark; Masaryk, Thomas
Delivery wire fracture of flow-diverter stents are rare but have been described. We describe a video case of a successful technique to retrieve such a fractured delivery wire by using a balloon microcatheter and the intermediate catheter when other proven methods may fail.